Analisis Kualitas Pelayanan dengan Metode Servqual (Service Quality) dan IPA (Importance Performance Analysis) - Gerson, Tarigan Ian; Safar, La Ode Ahmad; Utomo, Dutho Suh (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to measure customer satisfaction with hotel service quality using the SERVQUAL method. Gap analysis was conducted across five service dimensions: tangibles (0.0002), empathy (0.013), reliability (0.016), responsiveness (-0.093), and assurance (-0.008), with an average gap of -0.014. Furthermore, the study employed the Importance Performance Analysis (IPA) method to assess which attributes should be maintained and which require improvement. Based on the IPA method, the Cartesian diagram indicates that attributes prioritized for improvement in Quadrant I include: the size and security of the parking area (AS4) at -0.018, employees providing prompt and accurate service to customers (RES1) at -0.012, the speed of maintenance and repair services by employees (RES2) at -0.029, and the cleanliness of hotel rooms (TA5) at -0.09. Proposed improvements include expanding and installing a roof over the parking area, evaluating the service system, and conducting regular training for employees, particularly housekeeping staff, to ensure optimal room cleanliness.